1995
DOI: 10.1002/ijc.2910600216
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐α1 gene transfection completely abolishes the tumorigenicity of murine B16 melanoma cells in allogeneic DBA/2 mice and decreases their tumorigenicity in syngeneic C57BL/6 mice

Abstract: The murine B16 melanoma (H-2b) was transfected with a retroviral vector containing the mouse IFN-alpha 1 gene. IFN-alpha 1-transfected cells produced IFN-alpha in vitro and exhibited an altered phenotype characterized by a decreased rate of multiplication, enhanced expression of H-2 antigens, an antiviral state to VSV, and decreased pigmentation. Control and IFN-alpha 1-transfected cells were tested for their ability to grow in syngeneic (H-2b) C57Bl/6 and allogeneic (H-2d) DBA/2 mice. IFN-alpha 1-producing B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…2 Type I interferons, IFN-α and IFN-β, are known to have pleotrophic effects like inhibition of tumor cell growth, stimulation of the immune system, and inhibition of angiogenesis and tissue remodeling. [3][4][5][6][7][8] We and others have demonstrated significant growth inhibition and induction of apoptosis by IFN-β in cancer cells including colorectal cancer.. 7,[9][10][11][12] We have previously reported the induction of TRAIL following adenovirus mediated IFN-β gene therapy and IFN-β protein treatment in colorectal cancer cell lines. 13 In these cells, the induction of TRAIL appeared to be a crucial step in the IFN-β induced apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…2 Type I interferons, IFN-α and IFN-β, are known to have pleotrophic effects like inhibition of tumor cell growth, stimulation of the immune system, and inhibition of angiogenesis and tissue remodeling. [3][4][5][6][7][8] We and others have demonstrated significant growth inhibition and induction of apoptosis by IFN-β in cancer cells including colorectal cancer.. 7,[9][10][11][12] We have previously reported the induction of TRAIL following adenovirus mediated IFN-β gene therapy and IFN-β protein treatment in colorectal cancer cell lines. 13 In these cells, the induction of TRAIL appeared to be a crucial step in the IFN-β induced apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Rejection of the IFN-␣-producing tumor cells consistently led to the development of long-lasting tumor-specific immunity which, in some cases, was clearly mediated by CD8 + T lymphocytes. 8 Notably, in a recent study in which we specifically selected a highly metastatic mouse tumor resistant to therapy with large doses of IFN-␣/␤, we found that the genetically modified tumor cells expressing IFN-␣ were efficiently rejected by host-mediated mechanisms when injected into immunocompetent syngeneic mice, suggesting that there might be some advantages in transducing this cytokine gene with respect to the conventional therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In murine models, several studies with genetically modified tumor cells producing IFN-␣ have been previously reported, and the efficiency of IFN-␣ transduction for reducing tumorigenicity has been demonstrated. [3][4][5][6] Rejection of IFN-␣-transduced tumor cells depends on a CD8 + cell-mediated immune response. 3 T lymphocytes are the principal effector cells mediating the antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%